RELATIONSHIP OF STRUCTURAL LAYERS AND ONTIC LAYERS OF LANGUAGE COMPOSITION - Gyulzatyan, Davit (Foreign Languages for Special Purposes, 2023)
In recent decades, the understanding of hierarchical levels of language has been largely based on the theory of Emile Benveniste. Linguistic composition is the totality of ontological and structural (hierarchical) levels of language. Each of the hierarchical components of language is clearly localized at each of the ontic levels. In the work, an attempt is made to present a new concept of levels based on new principles by crossing the hierarchical and ontic layers of language. Such an approach also makes it possible to define linguistic disciplines, based on the divisions of the theory of language in the case of hierarchy, based on interdisciplinary relations in the case of ontic layers.
Keywords: justification function; syllable composition; word level; lexeme; phoneme; morpheme